Effect of addition of intrathecal preservative free magnesium sulfate with 0.5% bupivacaine heavy and fentanyl with 0.5% bupivacaine heavy on post-operative pain relief in patients undergoing hysterectomy - Gupta, Ankita; Neelima Tandon; Namrata Jain; Manmohan Jindal (Asian Journal of Medical Sciences, 2023)
Background: Spinal anesthesia is the most common neuraxial anesthesia for infraumblical surgeries. The use of various adjuvants has become popular in today’s scenario to enhance its quality. Aims and Objectives: The aim of this study was to evaluate the onset, duration of sensory and motor block, hemodynamic effects (if any), duration of post-operative analgesia, and adverse effects of fentanyl or magnesium given intrathecally with 0.5% bupivacaine heavy in patients undergoing hysterectomy. Materials and Methods: This prospective randomized double-blinded study was conducted in total sixty patients undergoing hysterectomy, divided into two groups of 30 patients each. Group F received 25 μg fentanyl with 3 mL 0.5% bupivacaine heavy and Group M received 100 mg magnesium sulfate with 3 mL 0.5% bupivacaine heavy. The onset and duration of sensory and motor blockade, duration of analgesia, hemodyamics, and side effects were assessed. Results: The mean time of onset of sensory and motor block was less in fentanyl (P<0.001). Duration of sensory, motor block, and duration of analgesia was more in fentanyl group (P<0.001), whereas incidence of side effects such as bradycardia, hypotension, and shivering was less in magnesium. Conclusion: Our study concluded that addition of fentanyl as adjuvant effectively augmented the quality of spinal anesthesia, but magnesium provided stable hemodynamics and lesser side effects as compared to fentanyl.